Reaching out to the academe a study on the reference services of academic archives in Metro Manila - Mariano, Randolf D.; Rey, Emma M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
In the Philippines, university libraries and museums have already proven their educational missions and core functions. Both have designed dynamic reference activities and educational outreach components to fulfill their respective missions. However, archivists are still addressing the need to improve reference services in academic archives.
This study was conducted to assess the reference service practices rendered by selected academic archives in Metro Manila. Fundamentally, it sought to attain the following objectives: (1) to know the information and resource materials in the selected academic archives; (2) to describe the procedures being employed by selected academic archives in providing reference services; (3) to find out the reference tools used to access materials in the selected academic archives; (4) to discover the reference activities and public programs employed by the selected academic archives in providing reference services in relation to intellectual access of archival materials; (5) to describe the utilization of access policy in regulating physical and legal access of archival materials in selected academic archives and; (6) to identify the problems encountered by academic archivists in rendering reference services. The study utilized a descriptive survey method. Survey questionnaires were used as the principal instrument for gathering data and follow-up interviews were rendered for data supplementation.
Based on the findings, the study concluded that: (1) reference services in academic archives were created to make available and accessible archival materials pertaining to administrative and academic missions and purposes of the university; (2) undergraduate students and administrators are the usual users of archives and history is the usual subject retrieved by the users; (3) academic archives perform step-by-step reference interview and different types of reference activities and public programs depending on the needs of the users; (4) academic archives have access policies for the users but lack detailed and well-defined legal access policies; (5) all academic archivists are familiar with laws, governing privacy, confidentiality, and freedom of information and strictly implement them; (6) academic archives perform user studies from time to time but lack in-depth evaluation, and; (7) the common problems encountered by reference archives are issues regarding trivial and not well-defined access policies, lack of physical space and reference room, lack of qualified personnel, and dearth of specialized reference tools that hindered intellectual access to archival materials.
Recommendation of this study include clear setting of academic archives in the university organizational structure; collaboration among academic archives in order to standardize reference service practices, and; evaluation of the information technology competencies of the archivists. Therefore, training of reference archivists is also recommended. In addition, information seeking behavior must be carefully studied to have a clearer picture of what reference service to offer to users. Finally, outreach programs should be instituted in order to improve the profile of academic archives.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Universities and colleges -- Philippines -- Manila Metropolitan Area; Archives -- Reference services -- Philippines -- Manila Metropolitan Area